Recruiting effects of Army advertising - Dertouzos, James N., 1950-; Dertouzos, James N., 1950-; Polich, J. Michael; Bamezai, Anil.; Chesnutt, Thomas W.; Rand eBooks (Santa Monica, CA : RAND, 1989)
This report analyzes the effects of Army advertising on recruiting. It uses an econometric analysis of information describing advertising patterns for the three-year period from 1981 to 1984. A model that controls for economic conditions, local area characteristics, the magnitude and direction of recruiter effort, and levels of other recruiting resources permits identification of the independent effects of different advertising purchases on the short-run supply of high-quality enlistments in the Army. The results show that, in general, advertising expenditures in a given month have a significant and immediate effect on the number of high-quality enlistments in the Army. Moreover, the advertising increases enlistments for as long as six months. The effects imply that the Army's national and local advertising programs compare favorably with other recruiting tools in terms of cost per high-quality enlistee.
"January 1989."
"National Defense Research Institute"--Cover.
This research was "prepared within RAND's Defense Manpower Research Center"--Preface.
Includes bibliographical references (p. 37-40).
Also available on the internet via WWW in PDF format.
Description based on print version record.
Keywords: United States. -- Army -- Recruiting, enlistment, etc. -- Statistics; Advertising -- Recruiting and enlistment -- United States -- Statistics; Electronic books